Studies of the Asian giant honey bee, Apis dorsata fabricius (Apidae) in the submerged Melaleuca forest of Vietnam - Tan, N; Tan, Nguyen Quang (2004)
﻿ This thesis examines the bee, the plant and the human communities in the submerged Melaleuca forests of southern Vietnam. Chapter 1 gives a general introduction to the taxonomy and evolution of the genus Apis (honey bees), the research area and the general objectives of the thesis. Chapter 2 deals with biology of the Asian giant honey bee, Apis dorsata Fabricius and presents new data on the sizes and ratios of the drone and worker cells; the weight of the queen, drone and worker; and the egg production of A. dorsata queens. Chapter 3 demonstrates that properties of nest sites; such as the diameter, slope, length of the nest site, remnants of beeswax from the previous colony, and the size of the open space in front of the nest site, are criteria in the selection of nest sites by A. dorsata colonies. Chapter 4 discusses the floral relations of A. dorsata and other insect visitors in the forest. Three types of partitioning within and among plants and insects in the Melaleuca forest are found. These are the partitioning of visitors by Melaleuca cajuputi and Nypa fruticans flowers, the partitioning of visitation time by the two sympatric honey bee species, A. dorsata and A. florea, and the partitioning of visitation time on Melaleuca and Nypa flowers by either honey bee species. Results of Chapter 5 show that there is temporal partitioning of flower sources among the sympatric Asian honey bee species (A. dorsata, A. cerana and A. florea ); however, there is a competition of flowers between the European bee (A. mellifera) and the Asian bee species. Chapter 6 discusses the important role of A. dorsata rafter beekeeping in forest protection, the conflicts between the beekeepers and new forest holders, and the economic efficiency of A. dorsata rafter beekeeping in comparison with those of A. mellifera and A. cerana beekeeping systems. Finally, Chapter 7 gives general conclusions of the thesis and recommendations for further study.